The Review of Interventions to Improve the Swallowing Function in the Elderly - Na-Yeon Tak; Hanna Gu; Hyoung-Joo Kim; Jun-Yeong Kwon; Hee-Jung Lim (The Korean Society of Dental Hygiene Science, 2023)
Background: Swallowing function deterioration is a common problem experienced by older adults worldwide. Many studies have been conducted to improve swallowing function in older adults; however, due to differences in intervention methods and study designs, it is difficult to draw a common conclusion. This study aimed to analyze trends and intervention methods in studies of swallowing function intervention for older adults conducted from 2010 to 2022, to establish a systematic approach for developing interventions to improve swallowing function in older adults and to provide evidence for this approach. Methods: Literature research was conducted for studies published between 2010 and 2022 that applied to swallow function interventions to adults aged 60 years or older. Databases including PubMed, Medline, RISS, Science On, KISS, and KCI were used. From a total of 1,164 articles searched using keywords, 20 articles were selected for final analysis. Results: The number of published articles steadily increased over time, and the intervention period was most commonly 6 or 8 weeks. The types of interventions included focused exercises to improve oral muscle strength in 12 articles and programs incorporating education, practice, and expert management in 8 articles. Among the focused exercises, tongue-strengthening exercises were most common in 4 articles. The evaluation variables for intervention effects were muscle strength evaluation, oral function evaluation, quality of life, and oral health and hygiene status. Muscle strength and oral function evaluations were statistically significant in focused exercise interventions, while the quality of life and oral health and hygiene status was significant in program interventions. Conclusion: This literature review is meaningful as a study that can be used to select the intervention period and program contents when planning an elderly swallowing intervention program.